Development and validation of a questionnaire to assess knowledge in patients with Atrial Fibrillation. (29th July 2021) - Gallagher, C; Rowett, D; Nyfort-Hansen, K; Simmons, S; Bulto, L; Middeldorp, ME; Lau, DH; Sanders, P; Hendriks, JM
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: Centre for Heart Rhythm Disorders Background: Education is critical to empower individuals to self-monitor and manage their condition. Significant variability exists in the provision of education for atrial fibrillation (AF), whilst individual patient factors including health literacy and education level attainment may impact on knowledge levels. Objective assessment of knowledge  may help to target education to areas of need, and result in improved patient outcomes. Objective: To describe the development and validation of a knowledge questionnaire for AF. Methods: A multidisciplinary expert team of healthcare professionals developed the questionnaire, in conjunction with consumers, with question content based upon areas deemed most critical to AF and related self-management. The multiple choice questionnaire consists of 20 items, each worth 5 points, to give a total score out of 100. The questionnaire assesses five domains specific to AF: general knowledge, complications, medications, risk factors and action. The questionnaire was developed in English. The questionnaire was tested on 10 randomly selected patients with AF for face validity and 19 healthcare professionals for content validity. The final version was completed by 454 individuals with AF. Exploratory factor analysis was used to determine construct validity with factor loadings of 0.40 and above considered acceptable. Reliability was assessed using Cronbach's alpha, with a value greater than 0.7 acceptable. Results: Face and content validity were considered acceptable, after minor changes to wording. The cohort of 454 individuals with AF had a mean age of 66.9 ± 12 years and 43% were female. Mean (SD) total score was 57.7 ± 15.8. Exploratory factor analysis was undertaken using the principal components method. This resulted in a Kaiser–Meyer–Olkin Measure of Sampling Adequacy of .64 and a Bartlett"s Test of Sphericity being significant at 0.00. Seven factors were selected and analysed using principal component analysis with varimax rotation. All items loaded on one of the seven factors. Internal consistency demonstrated a Cronbach's alpha of 0.65. Conclusion: The Atrial Fibrillation Knowledge Questionnaire is a valid measure to assess knowledge in individuals with AF.